Answer:
6
Step-by-step explanation:
-3 x (8 + [-10]) =
-3 x (8 - 10) =
-3 x -2 =
6
HOpe that helps!
Oliver is incorrect because if he were correct he would learn for 2 hours and 15 minutes because, 45 minutes * 3= 2:15 minutes.
The equation given in the question is
3(3x - 1) + 2(3 - x) = 0
9x - 3 + 6 - 3x = 0
6x + 3 = 0
6x = - 3
x = - (3/6)
= - (1/2)
So the value of x as has been determined above is -1/2. I hope the procedure is clear enough for you to understand.<span>You can
always use this method for solving problems that are similar in type without
requiring any help from outside. </span>
The answer is 0.00010224...
Good evening
Answer:
<h2>39</h2><h2 />
Step-by-step explanation:
9(14-5)-42 = 9×9 - 42
= 81 - 42
= 39
________________
:)